APPLICATIONS OF GIGER AND DAVIDHIZAR'S TRANSCULTURAL NURSING THEORY IN INDONESIA - Reini Astuti; Agaton Manuel T. Alzate (Jurnal Kesehatan Budi Luhur)
Indonesia has a diversity of cultures and ethnic groups. Indonesia is an archipelagic country that includes more than 17,000 islands inhabited by around 255 million people, making Indonesia the fourth most populous country in the world. This figure also implies that many cultural, ethnic, religious and linguistic diversity can be found in this country. The culture varies greatly, from Hindu rituals practised daily on the island of Bali to the (partial) implementation of sharia law in Aceh and the hunter-gatherer lifestyle of the Mentawai people.